A Simple Structure Conjugated Polymer for High Mobility Organic Thin Film Transistors Processed from Nonchlorinated Solvent - Zhongli Wang; Xianneng Song; Yu Jiang; Jidong Zhang; Xi Yu; Yunfeng Deng; Yang Han; Wenping Hu; Yanhou Geng (Advanced Science, 2019)
Abstract Herein, a simple structure, nonchlorinated solvent processable high mobility donor–acceptor conjugated polymer, poly(2,5‐bis(4‐hexyldodecyl)‐2,5‐dihydro‐3,6‐di‐2‐thienyl‐pyrrolo[3,4‐c]pyrrole‐1,4‐dione‐alt‐thiophene) (PDPPT3‐HDO), is reported. The enhanced solubility in nonchlorinated solvent is realized based on a denser alkyl side chains strategy by incorporating small size comonomer thiophene. An associated benefit of thiophene comonomer is the remarkable structural simplicity of the resulting polymer, which is advantageous for industrial scaling up. The alkyl side chain density and structure of PDPPT3‐HDO can efficiently control the self‐assembly properties in solution and film. By bar coating from o‐xylene solution, PDPPT3‐HDO forms aligned films and exhibits high hole mobility of up to 9.24 cm2 V−1 s−1 in organic thin film transistors (OTFTs). Notably, the bar‐coated OTFT based on PDPPT3‐HDO shows a close to ideal transistor model and a high mobility reliability factor of 87%. The multiple benefits of increased side chain density strategy may encourage the design of high mobility polymers that meet the requirements of mass production of OTFT materials and devices.